THE PREVALENCE OF CO-PRODUCTION OF ESBL, AMPC AND METALLO-b- LACTAMASES IN KLEBSIELLA PNEUMONIAE ISOLATES, IN A TERTIARY LEVEL HEALTH CARE PROVIDING FACILITY IN HARYANA - MEENU GARG; RAMA SIKKA; ANTARIKSH DEEP; UMA CHAUDHARY (International Journal of Pharma and Bio Sciences, 2015)
Klebsiella pneumoniae is a pathogen primarily capable of causing urinary tract infections and pneumonia in otherwise healthy people. Most of the strains are frequently resistant to numerous antibiotics, responsible for conferring multidrug resistance. This study was conducted to determine the prevalence of extended spectrum β-lactamases (ESBL), AmpC b-lactamases and metallo β-lactamases (MBL) and their coproduction by phenotypic methods. Out of 100 K. pneumoniae isolates, 41%, 45% and 36% were found to be ESBL producers, AmpC producers and MBL producers respectively. Co-production of all three β – lactamases i.e. ESBL, AmpC and MBL was observed in 3 % of the isolates. The high prevalence of β- lactamases emphasises the need for an early detection of the β-lactamase producing organisms, which can help in initiating an appropriate antimicrobial therapy and in avoiding the development and the dissemination of multidrug resistant strains.